Generation of Perfect Cylindrical Vector Beams With Complete Control Over the Ring Width and Ring Diameter - Prabin Pradhan; Manish Sharma; Bora Ung (IEEE Photonics Journal)
We propose the generation of high-purity perfect cylindrical vector beams (PCVB) using the Fourier transformation of Bessel–Gauss vector beams. The demonstration of PCVBs is implemented via an interferometric method employing a spatial light modulator that allows a fully independent control of the ring diameter ( $R_D$ ) and ring width ( $R_W$ ) of the PCVB. The proposed scheme enables to generate different types of cylindrical vector beams with precise user-defined transverse dimensions. The dynamic control of the ring width, ring diameter, and the specific type of PCVBs desired is theoretically as well as experimentally demonstrated. The proposed experimental setup can not only be employed in the generation of arbitrary PCVB, but also in perfect vortex beams. The ability to generate fully tailorable cylindrical vector beams and vortex beams has implications for the efficient launch of exotic optical modes in specialty fibers, in the field of optical tweezers as well as for superresolution microscopy.